PERTEMerch: stimulate creativity and entrepreneurial skill - UiTM, Faculty of Applied Sciences (Faculty of Applied Sciences, 2021)
PERTEMerch was organised by the committees of Persatuan Teknologi Makanan (PERTEMA), UiTM Shah Alam.